2005
DOI: 10.1046/j.1540-8167.2005.40559.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temporal Application Parameters on Lesion Dimensions During Transvenous Catheter Cryoablation

Abstract: The dimensions of lesions created by catheter cryoablation are affected by mode of cryoablation application and electrode orientation. Increasing the duration of application, employing multiple freeze-thaw cycles at shorter cycle durations, and orienting the catheter to enhance/increase tissue contact can create a larger lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 15 publications
2
42
1
Order By: Relevance
“…It has been shown that the use of 6-mm tip catheters relates to a lower recurrence rate compared to 4-mm tip [11,26]. On the other hand, the role of number and duration of cryoenergy applications on long-term outcome is controversial [15,27,28]. Notably, our results suggest that the quality of the cooling dynamics may be assessed and seems more relevant compared to the general quantity of cryoenergy delivered.…”
Section: Cooling Dynamicsmentioning
confidence: 79%
“…It has been shown that the use of 6-mm tip catheters relates to a lower recurrence rate compared to 4-mm tip [11,26]. On the other hand, the role of number and duration of cryoenergy applications on long-term outcome is controversial [15,27,28]. Notably, our results suggest that the quality of the cooling dynamics may be assessed and seems more relevant compared to the general quantity of cryoenergy delivered.…”
Section: Cooling Dynamicsmentioning
confidence: 79%
“…In an in vitro study, Tse et al . reported that a horizontal catheter tip‐to‐tissue orientation produced larger lesion diameters but not lesion depth compared to a vertical angle 20 . Longer freezing duration (i.e., 5 vs 2.5 minutes) was the only independent predictor of depth.…”
Section: Discussionmentioning
confidence: 90%
“…1,9,1215 Holman et al . 16 first reported the occurrence of undesired AVB during selective cryosurgical ablation (−60°C) of the perinodal tissue that completely resolved over time if the cryothermic exposure was immediately terminated.…”
Section: Discussionmentioning
confidence: 99%
“…First, lesion size can depend on several conditions such as electrode orientation, contact pressure, and blood velocity that were not controlled for in the present study. 12,13 For this reason, application duration was randomly assigned to partially overcome this limitation. Second, more than one cryoablation application was needed to obtain AVB in two-thirds of the experiments.…”
Section: Discussionmentioning
confidence: 99%